2010
DOI: 10.1111/j.1464-410x.2010.09348.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity might not be a risk factor for female sexual dysfunction

Abstract: group 3 ( > 40). All women were evaluated with Female Sexual Function Index (FSFI) questionnaire and Beck Depression Inventory (BDI). In addition, serum levels of follicle-stimulating hormone, luteinizing hormone, prolactin, dehydroepiandrosterone-SO 4 , free testosterone, 17 α -hydroxyprogestrone, androstenedione, oestradiol, free thyroxine and thyrotropin were determined. RESULTSThe mean FSFI scores were not statistically significant between control and obese patients ( P = 0.29). FSD was diagnosed in 50% (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
5
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 30 publications
4
47
5
2
Order By: Relevance
“…Likewise, depression as a consequence of BMI was also found to have a negative association with sexual functioning in pre-menopausal women [72]. A similar relation might be expected in women with PCOS.…”
Section: Sexual Satisfaction Attractiveness and Self-worthsupporting
confidence: 62%
“…Likewise, depression as a consequence of BMI was also found to have a negative association with sexual functioning in pre-menopausal women [72]. A similar relation might be expected in women with PCOS.…”
Section: Sexual Satisfaction Attractiveness and Self-worthsupporting
confidence: 62%
“…Women with CS had significantly lower FSFI scores, while the median of total FSFI scores for patients with CS and the control group were 16.6 [IQR: [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and 26.8 [IQR: 25.5-30.4], respectively (p<0.001). The arousal, lubrication, the ability to achieve orgasm, pain and satisfaction subdomains of FSFI were significantly lower in patients with CS (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…[21,22] In a previous study by our group, we showed that obesity did not affect sexual function in women. [23] Likewise, Yaylali et al [21] investigated FSD in women who were obese and overweight and found no significant difference between obese patients and the nonobese control group in terms of total FSFI scores. All these studies used the same FSFI survey with ours which has been validated for Turkish population by Oksuz et al [12] .…”
Section: Discussionmentioning
confidence: 99%
“…human bodies can produce genital vasocongestion and orgasm,' there is little to justify the claim that, 'absence of these features constitutes a "disorder"' (Tiefer, 2004: 190). Yet, this is how disorder is constituted, despite the absence of any acknowledgement of the interpersonal and social factors affecting sexual behaviour and activity or a widely-agreed standard for measuring 'function' or 'dysfunction' (Tiefer, 2004: 192 see also Adolfsson, 2004;Kadioglu, 2010;Kolotkin, 2006;Larsen, 2008;Østbye, 2011 for the range of scales used to measure elusive sexual 'satisfaction'). This is the model of sexual (dys)function reflected in the medical articles analyzed.…”
Section: Critiquing Failurementioning
confidence: 99%